PENGARUH SUBSTITUSI STARTER YOGHURT DENGAN CAIRAN TAPE KETAN TERHADAP KARAKTERISTIK YOGHURT YANG DIHASILKAN - Suriasih, Ketut (Agrotekno; Vol. 11, No. 2 Januari 2005, 2012)
Fermented milk as yoghurt has already known worl wide. Consumers in Indonesiacan not accepted the acidity flavour of this yoghurt so much. Therfore substitution ofyoghurt sterter by tape culture filtrate could be taken since tape culture filtrate is sweet andhas arome that accepted so much by the Indonesian. Therefore, it is necessary to investigatethe concentration of substitution of yoghurt starter by tape culture filtrate to obtain theprefferred yoghurt. This experiment done to find out the effect of subsstitution of yoghurtstarter by tape culture filtrate on characteristics yoghurt obtained. A randomized blockdesign with 5 treatments and 2 replications was applied to this experiment Parametersobserved were pH, glocose and lactose consentration, texture, taste and overaal acceptanceof yoghurt obtained. The result showed that treatments significantly affect (P<0,05) the pH,glucose and lactose concentration, texture, taste and overall acceptance of the yoghurtresulted. And substitution of 50% yoghurt strter with tape ketan culture filtrate resulted themost likely yoghurt.
Keywords: Yoghurt, tape ketan